Cholecystoduodenal Stenting: An Option in Complicated Acute Calculous Cholecystitis in the Elderly Comorbid Patient - Brady Bonner; Nicholas I. Brown; Varghese Pynadath Joseph; Manju Dashini Chandrasegaram (Case Reports in Surgery)
We describe the course of an 84-year-old lady with acute calculous cholecystitis. She was unable to have a cholecystectomy due to multiple comorbidities including morbid obesity, type 2 diabetes, Guillain–Barrè syndrome, chronic sacral pressure ulcer, and severe cardiac disease. Conservative treatment with intravenous antibiotics was initially successful; however, she subsequently re-presented with an empyema of the gallbladder. She was readmitted for further intravenous antibiotics and underwent percutaneous gallbladder drainage. The patient did not want a permanent catheter for drainage, nor the prospect of repeat drainage procedures in the future for recurrent cholecystitis. Following a discussion of the rationale and risks involved with other minimally invasive techniques, she underwent cholecystoduodenal stent placement following disimpaction and removal of cystic duct stones. The procedure restored antegrade gallbladder drainage, and at 18 months she remains symptom-free from her gallbladder. Long-term management of recurrent cholecystitis in elderly comorbid patients commonly includes permanent cholecystostomy or repeated percutaneous gallbladder drainage, both of which can be poorly tolerated. Permanent cholecystoduodenal stenting is a reasonable alternative in carefully considered patients in whom the benefits outweigh the risks. We describe our experience with cholecystoduodenal stenting and discuss some of the concerns and considerations with this technique.